Relevansi pemikiran al-ghazali tentang belajar Dan pembelajaran bagi pendidikan islam kontemporer - Halimah; Mayasari; Ali Maulida (Yayasan Azhar Amanaa Yogyakarta, 2026)
Contemporary Islamic education faces the challenge of balancing academic knowledge with moral and spiritual values in learners’ development. This study aims to analyze the concept of learning and instruction from the perspective of Abū Ḥāmid al-Ghazālī and to identify its relevance to contemporary Islamic educational practices. The main issue addressed is how to integrate al-Ghazālī’s principles into modern Islamic education, which tends to emphasize cognitive aspects without neglecting moral and spiritual dimensions. The research method employed is a literature review, analyzing al-Ghazālī’s classical works as well as relevant academic articles and journals on contemporary Islamic education. The findings indicate that al-Ghazālī’s educational concept, which emphasizes the balance between worldly (dunyāwī) and otherworldly (ukhrawī) knowledge, can be implemented within a holistic Islamic education design. The study produces a conceptual synthesis in the form of an al-Ghazālī-based holistic learning model consisting of spiritual objectives, integration of knowledge and faith, student ethics, teacher exemplarity, reflective learning, and character-based evaluation. The implications of this study highlight the necessity of curriculum reform in Islamic education that integrates moral and spiritual values with ethically grounded educational technology, as well as strengthening the role of teachers as both intellectual and spiritual mentors in the learning process. This study offers a conceptual framework for transforming al-Ghazālī’s thought into contemporary Islamic educational design oriented toward intellectual, moral, and spiritual balance.